KESULITAN MAHASISWA PPG PENDIDIKAN FISIKA FKIP UNSYIAH DALAM MELAKSANAKAN PROGRAM PENGALAMAN LAPANGAN DI BANDA ACEH - rahmad Maulidi Tigana; Susanna Susanna; Soewarno S (FKIP Unsyiah, 2017)
This research aimed to determine the difficulties of PPG students of Physics education FKIP Unsyiah in implemented teaching experience program in Banda Aceh. This research is a descriptive research type using a qualitative approach. The subject of this research were PPG student of physics education FKIP Unsyiah who implemented the teaching experience program in Banda Aceh in the academic year 2016/2017 which amounted to 15 students. Data collection in this research used questionnaire technique and data analysis technique used percentage test. Based on the data analysis result, it is found that the difficulties of PPG students of physics education FKIP Unsyiah in conducting lesson opening activities were low, the difficulties in mastering the learning material were low, the difficulties in implementing educational learning strategies were low, the difficulties in applying the scientific approach were very low, the dificulities in resourcing utilization and instructional media were low, the difficulties in involving students in learning were very low, and the difficulties in closing lessons activities were very low. Overall the difficulty level of PPG students of physics education FKIP Unsyiah in implemented the teaching experience program (PPL) were low with percentage of difficulty was 36,8%, which showed that PPG students of physics education FKIP Unsyiah have no difficulties in implementing teaching experience program (PPL) in Banda Aceh.